JNK and Jag1/Notch2 co-regulate CXCL16 to facilitate cypermethrin-induced kidney damage - Changjiang Liu (Ecotoxicology and Environmental Safety, 2022)
Cypermethrin (CYP), a widely-used composite pyrethroid pesticide, has underlying nephrotoxic effects. To elucidate potential roles of the MAPK pathway, the Jag/Notch pathway, and miRNAs in CYP-mediated kidney lesion, Sprague-Dawley rats and glomerular mesangial cells were used in this work. Results displayed that β-CYP abnormally altered renal histomorphology and ultrastructures, induced renal DNA damage, and impaired renal functions, as evidenced by the increase in plasma levels of Cys-C and β2-Mg. β-CYP activated the JNK/c-Jun pathway by inducing ROS and oxidative stress. Meanwhile, β-CYP changed the miRNA expression profile, miR-21–5p showing the most significant increase. Moreover, the Jag1/Notch2/Hes1 pathway was directly targeted by miR-21–5p, the mRNA and protein expression of Jag1, Notch2, and Hes1 being declined in vivo and in vitro. The chemokine CXCL16 was induced by β-CYP, accompanied by the inflammatory factor production and inflammatory cell infiltration in kidneys. The specific JNK inhibitor, Jag1 overexpression, Hes1 overexpression, bidirectional Co-IP, ChIP, and CXCL16 silencing demonstrated that CXCL16 co-regulated by the JNK/c-Jun and Jag1/Notch2/Hes1 pathways elicited renal inflammation. Collectively, our findings indicate that β-CYP is of nephrotoxicity and it not only directly changes renal histomorphology and ultrastructures, but induces CXCL16 to trigger renal inflammation via the JNK/c-Jun and Jag1/Notch2/Hes1 pathways, finally synergistically contributing to kidney damage.